The ITIL process manual: key processes and their application - Persse, James R.; Chittenden, Jane (Zaltbommel, Netherlands : Van Haren Publishing, 2012)
This practical guide is a great solution to address the key problem how to implement ITIL and ISO 20000 when initial training has been completed. It supports the basic approaches to the fundamental processes. Small- to medium-sized companies will find the concise, practical guidance easy to follow and implement.
Keywords: Information technology -- Management. .; Information technology -- Quality control -- Standards; IT infrastructure library